ORGANIZATIONAL MECHANISM OF MANAGING THE DEVELOPMENT OF SOCIAL ENTREPRENEURSHIP IN UZBEKISTAN - Narzullaev Elmurod Shukhrat ogli (Research Trend in Technology and Management, 2023)
The main objective of this study is analyzing the capability of improving and developing organizational methodological mechanism of managing the development of social entrepreneurship in Uzbekistan. The theoretical basis of the scale is supported by empirical research in the social sector. On other hand, finding out both strengths and weaknesses on managing and developing environmental social entrepreneurship in our country also was our main aim in this article.